Professor Spira Strahinjić (1925 – 2022) – Pioneer of Serbian and Yugoslav Nephrology - Babić, Strahinja; Babić, Katarina; Babić, Nevena; Jevremović, Aleksandar; Babić, Rade R.; Stanković-Babić, Gordana (Medical Word, 2024)
Professor Dr. Spira Strahinjić (August 30, 1925, village of Orane, Kingdom of Yugoslavia - January 25, 2022, Niš, Republic of Serbia) was and will remain a doyen and legend of Serbian and Yugoslav medicine and beyond, a pioneer of Serbian and Yugoslav nephrology, visionary and strategist of the development of nephrology in Niš, Serbia and Yugoslavia, creator and founder of the Institute for Nephrology and Hemodialysis of the Faculty of Medicine of the University of Niš (which today bears his name), founder and initiator of the development of a large number of healthcare institutions for nephrology and hemodialysis in the south of Serbia, In Kosovo and Metohija and Montenegro, initiator of the first kidney transplant in the south of Serbia, one of the founders of BANTAO, patriot and revolutionary, participant of the National Liberation Movement (1941-1945), oriented and oriented towards the young man, the young doctor, always on the side of the students and student ideas of Niš , Serbia and Yugoslavia.